THE IMPACT OF ENVIRONMENTAL CHANGES ON CRIME PATTERNS: A GEOGRAPHICAL ANALYSIS - Singh, Taniya (ShodhKosh: Journal of Visual and Performing Arts, 2022)
Environmental transformations—ranging from climate shifts and land use changes to urban expansion—have been increasingly recognized as influential factors in shaping crime patterns. These changes may affect criminal behavior by altering resource availability, disrupting social structures, or reshaping the physical environment. This study undertakes a geographical analysis of how such environmental dynamics correlate with variations in crime across India. Drawing on a multidisciplinary literature review, the paper identifies diverse forms of environmental change—including climate variability, urbanization, natural disasters, and degradation—that have been empirically linked to fluctuations in crime rates. Utilizing statistical and spatial techniques, the study analyzes secondary data to examine the strength and direction of these associations, with particular attention to regional variations in the environmental-crime nexus. The findings reveal that environmental change does not uniformly influence crime; rather, its impact is mediated by geographic, socio-economic, and infrastructural conditions. By highlighting these spatial disparities, the paper contributes to a more nuanced understanding of the environment-crime relationship and underscores the need for place-based, interdisciplinary policy interventions. The study concludes with recommendations for integrating environmental and criminological planning into future urban development and disaster resilience frameworks.